Răspuns :
a)
[tex] \frac{1}{3} - \frac{2}{3} = \frac{1 - 2}{3} = \frac{ - 1}{3} = - \frac{1}{3} [/tex]
c)
[tex] - \frac{1}{3} - ( - \frac{2}{3} ) = - \frac{1}{3} + \frac{2}{3} = \\ \\ \frac{ - 1 + 2}{3} = \frac{1}{3} [/tex]
b)
[tex] - \frac{1}{3} + ( - \frac{2}{3} ) = - \frac{1}{3} - \frac{2}{3} = \frac{ - 1 - 2}{3} = - \frac{3}{3} = - 1[/tex]
d)
[tex] {}^{3)} \frac{1}{5} + ( - \frac{3}{15} ) = \frac{1 \times 3}{5 \times 3} - \frac{3}{15} = \\ = \frac{3}{15} - \frac{3}{15} = 0[/tex]
e)
[tex] {}^{4)} - \frac{1}{2} + ( - \frac{3}{8} ) = - \frac{1 \times 4}{2 \times 4} - \frac{3}{8} = \\ \\ = - \frac{4}{8} - \frac{3}{8} = \frac{ - 4 - 3}{8} = - \frac{7}{8} [/tex]
f)
[tex] {}^{2)} - \frac{1}{5} - ( - \frac{7}{10}) = - \frac{1 \times 2}{5 \times 2} + \frac{7}{10} = \\ \\ = - \frac{2}{10} + \frac{7}{10} = \frac{ - 2 + 7}{10} = \\ \\ = \frac{5}{10} {}^{(5} = \frac{5 \div 5}{10 \div 5} = \frac{1}{2} [/tex]